041: INVESTING IN RELATIONSHIPS AND STRATEGIES FOR ENGAGEMENT: THE CAPACITY OF ACADEMIA TO EFFECTIVELY INFLUENCE HEALTH POLICY IN KENYA. (24th August 2015) - Jessani, Nasreen S; Kennedy, Caitlin E; Bennett, Sara C
Abstract : Background: Universities aim to build technical capacity, generate new knowledge and use both for the advancement of society. However, challenges in bridging the gap between research, policy and practice often hinder this intended impact. The importance of relationships and effective strategies for academic-policymaker engagement to overcome these challenges, while important, often remain elusive, suffer from unmet expectations, and subject to mutual misperceptions. Objectives: In order to strengthen the capacity of academia to effectively influence health policy, we explore the networks and experiences of academics and policymakers in Kenya. Methods: We conducted a quantitative policy network mapping and analysis of academic faculty across 6 Schools of public health to identify knowledge brokers (KBs) and other key actors. We complemented this with semi-structured interviews with 12 academic faculty and 11 national health policymakers from within the network to uncover and explore key themes. Result: Six academic-policymaker networks emerged, identifying 7 KBs across 124 faculty. Academic faculty employed a greater array of strategies for leveraging these relations and enhancing engagement compared to policymakers including traditional dissemination of research results, and more creative honorary appointments for policymakers, amongst others. While the intention and capacity to engage across both types of institutions varied greatly, policymakers highlighted multiple strategies underutilized by academia thereby confirming different worldviews on effective engagement. Conclusion: Engagement between academics and policymakers in Kenya requires a delicate balance between leveraging individual relationships and establishing sustained institutional partnerships. Additionally, a combination of deliberate and opportunistic strategies is required from both sides. SPH deployment of personnel and skills for effective academic-policymaker engagement and deliberate investment in capacity building for relationship management and knowledge translation can enhance sustainable mechanisms for (i) increasing policymaker interest and investment in health systems research, (ii) moving innovations from research into action, (iii) recognizing academia as a source of socially-driven and practically-relevant knowledge, and (iv) reinforcing academic-policymaker partnerships.